Improved limits on lepton-flavor-violating τ decays to ℓ, ρ, K*, and K̄* - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2009)
We search for the neutrinoless, lepton-flavor-violating tau decays τ-→-V0, where is an electron or muon and V0 is a vector meson reconstructed as →K+K-, ρ→π+π-, K*→K+π-, K̄*→K-π+. The analysis has been performed using 451fb-1 of data collected at an e+e- center-of-mass energy near 10.58 GeV with the BABAR detector at the PEP-II storage rings. The number of events found in the data is compatible with the background expectation, and upper limits on the branching fractions are set in the range (2.6-19)×10-8 at the 90% confidence level. © 2009 The American Physical Society.